مفهوم الدين بين علماء اإلسالم وعلماء الغرب - رابح, مرزوق; عماد, فرحات; عرعار, محمد عبد العزيز (جامعة الوادي university of eloued, 2017)
ملخص الدراسة: ة فطرية فيإن الدين غريزأعماق البشر منذ العهد والميثاقالذيقطعه اهلل على الخلق األول؛فال نكاد نجد أمة دون دين؛ع الدين محلولما كان موضواسةدر الكثيرمن علماء العقيدة والفالسفة،مسلمين كانوا أوغربيين، ما كان لنا إال أن اءنجمع آرهم فيذلك من تعريف وماهية له،ووجوده في حياة األمم،وقد لُخّص كل ع عند علماء اإلسالم وكذا عند علماءاسة هذا الموضوما يتعلق بذلك من خالل در الغرب. Study Summary: Religion is innate instinct in the depths of human beings since the Covenant and the CharterWhich God made on the first creation, We hardly find a nation without religion , As it is the subject of religion is the subject of the study of many scholars of faith and philosophers , Muslims or Westerners , We could only gather their opinions in that definition and what it meant , and his presence in the life of nations , All of this has been summed up in the study of this subject by the scholars of Islam as well as by the scholars of the West.
مقارنة